Fenomena Hukum Islam di Masa Modern; Upaya Harmonisasi antara eksistensi dan Relevansi - Jihad Khufaya; Muhammad Kholil; Nurrohman Syarif (Mutawasith: Jurnal Hukum Islam, 2021)
Islamic law is often identical with the number of Islamic rules and doctrines regarding a number of static and standardized daily problems of Muslims. However, it often gives birth to various nuances of new thinking, in response to the emergence of a number of contemporary challenges and problems that make Islamic law seem dynamic. How far is the existence of Islamic law with its stability without being trapped in a stagnant attitude, and whether Islamic law in modern times is still relevant to Islamic law revealed by Allah SWT. and to what extent it must accommodate the various dynamics of new thinking without having to reduce the eternal and universal values and principles of Islam, is very important to put forward